Forty-Two Percent of Patients Undergoing Arthroscopic Shoulder Surgery Are Using Psychotropic Medications - Michael R. Cesarek, M.S.; Nicholas O. Gerard, III, M.S.; Brianna N. Griswold, B.S.; Mia V. Rumps, M.S.; Michael J. O’Brien, M.D.; Felix H. Savoie, III, M.D.; Mary K. Mulcahey, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To determine the prevalence of psychotropic medication use in patients undergoing shoulder arthroscopy at a single institution and to identify the most common medications and classes of drugs being taken in this specific patient population. Methods: We conducted a retrospective chart review of patients treated by 3 fellowship-trained orthopaedic sports medicine and shoulder surgeons between 2019 and 2021. All patients who underwent shoulder arthroscopy during this period were included. The following data were collected: age, sex, laterality of surgery, prior surgical procedures on the operated shoulder, specific surgery performed, and use of psychotropic medications. Drug categories included anticonvulsants, antidepressants/anxiolytics, sedative hypnotics, stimulants, antipsychotics, and multiple psychotropic drugs. Psychotropic medications were included if they were listed as being taken at any time in the patient’s chart (“taking”) within a 6-month window prior to surgery. Results: Of the 1,279 patients (828 male and 451 female patients) whose charts were reviewed, 534 (41.8%) were prescribed at least 1 psychotropic. Of the 453 patients treated in 2021, 201 (44.4%) were taking at least 1 psychotropic. Similarly, 152 of the 397 patients treated in 2020 (38.2%) and 181 of the 429 patients treated in 2019 (42.2%) were found to be taking at least 1 psychotropic. Among the 1,279 patients included, 282 of 828 male patients (34.1%) were prescribed psychotropic drugs compared with 252 of 451 female patients (55.9%, P = .001). From 2019 to 2021, 137 of the patients using psychotropic drugs (25%) were prescribed anticonvulsants/mood stabilizers; 105 (19%), antidepressants; 75 (14%), sedative hypnotics; 23 (4%), stimulants; 4 (1%), antipsychotics; and 190 (35%), multiple psychotropics. From 2019 to 2021, the rate of antidepressant/anxiolytic and/or sedative hypnotic prescription psychotropic drug use increased from 28% to 30.5% (P = .42). Conclusions: This study showed that a large portion of patients undergoing shoulder arthroscopy were taking psychotropic medications. Furthermore, we found that female patients had significantly higher utilization of these medications compared with male patients. Clinical Relevance: Understanding the prevalence of these medications in orthopaedic patients is essential for surgeons to take into consideration to limit preoperative, intraoperative, and postoperative complications, as well as optimize patient outcomes.